Determine of Employee Performance Study Case PT Interplex Precision Batam - Lestari, Nanik; Sondang Lusiomy Hutasoit, Rina (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research aims to determine the effect of work discipline and motivation on employee performance. Using a descriptive quantitative approach and processed with the SPSS version 20 application, the research involved 48 employees of PT Interplex Precision Batam as samples. The primary data collection method uses a questionnaire with the application of quantitative multiple regression analysis. The results of this research, both work discipline and motivation, have a significant partial and simultaneous positive influence on employee performance. Discipline and work motivation factors are able to explain around 61.9% of the variation in employee performance, while the remaining 38.1% is influenced by other variables not in this study, such as leadership and work environment conditions and others.